Uji Tuberkulosis Laten Pada Kontak Serumah Pasien BTA Positif Dengan Metode Mantoux Test - Norma Tiku Kambuno; Yunita Helmina Senge; Agustina W. Djuma; Elisabeth N. Barung (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2019)
Background. Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis. Latent tuberculosis is one of the conditions that occur when exposed to TB bacteria but does not show clinical symptoms. Vulnerable family members infected with TB due to difficulty avoiding contact with patients. The tuberculin skin test is one of the tests used to diagnose latent TB. The purpose of this study was to determine the description of latent TB in-home contact with smear-positive TB patients. Determine the relationship between latent TB with age, gender, education, occupation, and smoking status. Method. The type of research is correlation analytic research with a cross-sectional design with a total sample of 22 people. Results. Based on the results of the study as many as 15 people (68.2%) with induration > 10 mm, and 7 people (31, 8%) with induration <10 mm. While based on the results of statistical tests to see the relationship between the influence of age, sex, education level, occupation and smoking status with latent TB status obtained approx significant> 0.05. Conclusion. Thus the prevalence of latent TB at home contact with positive smear patients was 68.2% and there was no relationship between age, sex, education level, occupation and smoking status with TB status.